2014
DOI: 10.4055/cios.2014.6.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Bone Mineral Status in Adolescent Idiopathic Scoliosis

Abstract: BackgroundSeveral reports have suggested low bone mineral density (BMD) in patients with adolescent idiopathic scoliosis (AIS). We determined bone mineral status in patients with AIS to evaluate the effect of brace treatment on BMD.MethodsBMD was measured in 46 patients (mean age, 17.8 ± 4.9 years) with AIS (17 with brace and 29 without brace) by dual-energy X-ray absorptiometry scan and compared the results to an age-matched (mean age, 16.6 ± 3.9 years) control group (n = 54).ResultsThe AIS group had signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…Moreover, not only idiopathic scoliosis patients but also congenital and neuromuscular scoliosis patients were included in the current study. A study by Tahvildari et al [19] reported low BMD in patients with adolescent idiopathic scoliosis by using DEXA. Sadat-Ali et al [4] compared BMD values in patients with adolescent idiopathic scoliosis and their healthy siblings by using DEXA, and they found lower BMD values in the scoliosis group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, not only idiopathic scoliosis patients but also congenital and neuromuscular scoliosis patients were included in the current study. A study by Tahvildari et al [19] reported low BMD in patients with adolescent idiopathic scoliosis by using DEXA. Sadat-Ali et al [4] compared BMD values in patients with adolescent idiopathic scoliosis and their healthy siblings by using DEXA, and they found lower BMD values in the scoliosis group.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that also revealed an important association between scoliosis and osteopenia [12][13][14][15][16][17][18][19]. Other authors reported osteopenia as a cause of scoliosis worsening as it represents a risk of curve progression [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Since the Burner group first reported the association of low bone mineral density in AIS in 1982, scholars have focused on the relationship between osteopenia and AIS [6]. Most researchers have found that the incidence rate of osteopenia, which is the most common metabolic bone disease in adults but is rare in adolescents, is much higher in AIS than in adolescent populations, ranging from 20 to 38% [7, 8]. In addition, osteopenia is considered one of the causes of scoliosis curvature progression and curve severity [9, 10].…”
Section: Introductionmentioning
confidence: 99%